CircDOCK1 promotes the tumorigenesis and cisplatin resistance of osteogenic sarcoma via the miR-339-3p/IGF1R axis - Li, Shenglong; Liu, Fei; Zheng, Ke; Wang, Wei; Qiu, Enduo; Pei, Yi; Wang, Shuang; Zhang, Jiaming; Zhang, Xiaojing (Molecular cancer, 2021)
Circular RNAs (circRNAs), a class of noncoding RNAs (ncRNAs), may modulate gene expression by binding to miRNAs. Additionally, recent studies show that circRNAs participate in some pathological processes. However, there is a large gap in the knowledge about circDOCK1 expression and its biological functions in osteogenic sarcoma (OS). Differentially expressed circRNAs in OS cell lines and tissues were identified by circRNA microarray analysis and quantitative real-time PCR (qRT-PCR). To explore the actions of circDOCK1 in vivo and in vitro, circDOCK1 was knocked down or overexpressed. To assess the binding and regulatory associations among miR-339-3p, circDOCK1 and IGF1R, we performed rescue experiments, RNA immunoprecipitation (RIP), RNA pulldown assays and dual-luciferase assays. Moreover, we performed apoptosis assays to reveal the regulatory effects of the circDOCK1/miR-339-3p/IGF1R axis on cisplatin sensitivity. CircDOCK1 expression remained stable in the cytoplasm and was higher in OS tissues and cells than in the corresponding controls. Overexpression of circDOCK1 increased oncogenicity in vivo and malignant transformation in vitro. In the U2OS and MG63 cell lines, circDOCK1 modulated tumor progression by regulating IGF1R through sponging of miR-339-3p. Additionally, in the U2OS/DDP and MG63/DDP cell lines, cisplatin sensitivity was regulated by circDOCK1 via the miR-339-3p/IGF1R axis. CircDOCK1 can promote progression and regulate cisplatin sensitivity in OS via the miR-339-3p/IGF1R axis. Thus, the circDOCK1/miR-339-3p/IGF1R axis may be a key mechanism and therapeutic target in OS.